(untitled) (Research, Society and Development, 2022)
Blasting cleaning is widely used to prepare and clean surfaces, but the waste resultant is generally contaminated and recycling is an obstacle. The present study shows a technical route to reuse the carbon-steel shot blast waste to produce a solid material by powder metallurgy. The waste was selected by sieve and the particles mixtures were analyzed and selected with the aid of a simplex lattice experimental design and tap density. The characterization of waste particles was conducted in terms of their morphological shape and their technological and physical characteristics. The density of green compacts and sintered samples reached 7.11 g.cm-3 and 7.06 g.cm-3, respectively. After quenching and tempering heat treatments, the sintered steel exhibited a martensitic microstructure with a hardness of 430 HV. The sintered bodies showed promising properties and the powder metallurgy method for recycling shot blast waste was considered viable.